INTRICATE REALM OF GENDER DISCRIMINATION: EXPOSITION OF SHASHI DESHPANDE’S NOVEL ROOTS AND SHADOWS (International Journal of Food and Nutritional Sciences, 2022)
Gender equality is a human right that entitles all people, regardless of gender, to live in dignity and freedom. Gender equality is an essential prerequisite for comprehensive development and the alleviation of poverty. Women who are empowered play a crucial role in enhancing the health conditions, educational level, and economic efficiency of entire families and communities. Consequently, this leads to improved possibilities for future generations. The Millennium Development Goal also places significant focus on the advancement of gender equality and the empowerment of women. The acknowledgment of gender equality and women's empowerment as essential pillars for attaining development outcomes has gained widespread acceptance. This paper aims to examine the status of women empowerment and its determinants in India, specifically focusing on Shashi Deshpande's novel Roots and Shadows. The objective is to identify and analyze the key factors contributing to the existing inequalities within the novel, with a particular emphasis on the character of Indu. Indu represents the archetype of educated women who actively engage with society, disregarding restrictive social norms.